THE EFFECTIVENESS OF EXERCISE AND NUTRITION INTERVENTION PROGRAMMES TO PREVENT AND MANAGE OBESITY AMONG YOUNG POPULATION - Cholidah, Rifana (Faculty of Medicine Universitas Mataram, 2013)
Background:Childhood obesity has become a central chronic disease in this modern era. Early prevention and effective treatment of obese children and adolescents is mandatory. Surprisingly, there are limited shortand long-term studies determining targeted interventions particularly physical activity and dietary intervention in preventing and treating obesity among the young population. Further, the efficacy of physical activity and nutritional strategies to prevent and treat pediatric obesity remains unclear. Objective: This review aims to evaluate the effect of physical activity and dietary interventions in preventing and treating obese children and adolescents. Results: There are five main studies involved in this review. Most of the reviewed studies found significant reductions on body weight, body mass index and body fat, and improvement on aerobic fitness and endurance time. Conclusion: The data shows the short- and long-term beneficial effects of physical activity alone and in combined intervention with dietary-behavioural approaches to treat obesity among young population. However, some studies have flawed study design such as small sample size and unmatched participants in control group. Additional research considering behavioural, dietary and physical intervention, and costeffective approach for primary and community care are required.